Brazilian samba protocol for individuals with Parkinson's disease: A clinical non-randomized study - Tillmann A.C.* (2017)
© Ana Cristina Tillmann, Alexandro Andrade, Alessandra Swarowsky, Adriana Coutinho De Azevedo Guimarães. Originally published in JMIR Research Protocols (http://www.researchprotocols.org), 04.07.2017. This is an open-access article distributed under the terms of the Creative Commons Attribution License (https://creativecommons.org/licenses/by/4.0/), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work, first published in JMIR Research Protocols, is properly cited. The complete bibliographic information, a link to the original publication on http://www.researchprotocols.org, as well as this copyright and license information must be included.Background: In the 10 most populated countries in the world, Parkinson's disease (PD) affects more than 5 million individuals. Despite optimal treatment options already developed for the disease, concomitant involvement of other areas of health care plays an important role in complementing the treatment. From this perspective, dancing can be viewed as a non-drug alternative that can reduce falls by improving some motor skills, such as mobility, balance, gait, and posture, and can also improve the overall quality of life. Brazilian samba promotes improvement in motor and non-motor symptoms in individuals with PD, providing a new treatment option for this population. Objective: The main objective of this quasi-experimental study is to provide a 12-week samba protocol (2x/week) for individuals with PD and to compare its effects with the group without intervention. The hypothesis is that the Brazilian samba protocol will promote improvement in primary (motor) and secondary (non-motor) outcomes in individuals with PD. Methods: The sample will be selected at random from individuals diagnosed with PD in the city of Florianopolis (SC, Brazil). Sample size calculation was performed with the G*Power 3.1.9.2 software, with 0.447 effect size, at 5% significance level, power of 0.9, and test and sample loss of 20%. This yielded 60 individuals divided between the intervention and control groups. The questionnaires will be filled out before and after the dance intervention. The data collection for the control group will be held simultaneously to the intervention group. The classes will last for 1 hour, twice a week in the evening for 12 weeks, and all classes will be divided into warm-up, main part, and relaxation. Two-way analysis of variance with repeated measures and Sidak post-hoc comparison test will be used for a comparative analysis of the final results of the control group with the experimental group and of the within-group changes between pre- and postintervention period. Results: We expect to complete follow-up in September 2017. Conclusions: The major inspiration for this study was to encourage the creation of new rehabilitation programs that do not emphasize doctor involvement. This is a unique protocol for PD and we believe it can be an important tool to alleviate the motor and non-motor symptoms of individuals with PD. Dance is a simple activity depending on little equipment and few financial resources, facilitating its implementation and improving the cost-benefit relationship. In addition, activities that have a cultural aspect for the population in question, and which are pleasant, enable the participants to commit long term. This can enhance patient's compliance with the therapy, which is often a problem for many rehabilitation programs.